Peningkatan Hasil Belajar Peserta Didik pada Pembelajaran Pendidikan Pancasila Menggunakan Model Cooperative Learning Tipe Numbered Head Together di Kelas IV SD Negeri 15 Ulu Gadut Kota Padang - Rasima, Juina; Mansurdin, Mansurdin (Darul Yasin Al Sys, 2025)
This research is motivated by several problems found in the field, including teacher-centered learning, the dominance of lecture methods, and the implementation of group learning that is not optimal. This has an impact on students who feel bored, not confident, and less active in learning. This study aims to improve student learning outcomes in Pancasila Education learning using the Numbered Head Together type Cooperative Learning model in class IV of SDN 15 Ulu Gadut, Padang City. This research is a Classroom Action Research (CAR) which is carried out in two cycles, with 25 students as research subjects. Research data were collected through observation, tests, and non-tests. The results of the study showed an increase in: (1) assessment of teaching modules from cycle I meeting I by 87.5% (C) to 91.7% (B) at meeting II, and increased to 95.83% (A) in cycle II; (2) teacher and student activities in cycle I meeting I were 83.33% (C), increasing to 91.7% (B) in meeting II, and reaching 95.83% (A) in cycle II; (3) learning outcomes in the knowledge aspect in cycle I meeting I were 67.2% (D), increasing to 85.6% (C) in meeting II, and reaching 88% (B) in cycle II; (4) learning outcomes in the skills aspect in cycle I meeting I were 73.9% (D), increasing to 80.5% (C) in meeting II, and reaching 89% (B) in cycle II. The average overall learning outcomes increased from 71.704% (D) in cycle I meeting I to 81.36% (C) in meeting II, and reaching 88.836% (B) in cycle II. Based on these results, it can be concluded that the use of the Numbered Head Together type of Cooperative Learning model can improve student learning outcomes in Pancasila Education learning in class IV of SDN 15 Ulu Gadut, Padang City.